Infrared Wavefront Control Based on Graphene Metasurfaces. Issue 8 (18th June 2014) - Lu, Feifei; Liu, Baoan; Shen, Sheng
<x xml:space="preserve">Abstract</x> Metasurfaces, a new class of planar metamaterial, are attracting intensive attention due to their exceptional abilities to mold light. In this work, novel metasurfaces based on graphene nanoribbons are developed to control the wavefront of infrared light. The results show that these metasurfaces can create phase discontinuities between incident and scattered light, covering the phase range from 0 to about π while maintaining a relatively large amplitude for the scattered light. A cylindrical flat lens and anomalous refraction based on graphene nanoribbon metasurfaces are also demonstrated, paving the way to developing graphene‐based tunable devices for infrared wavefront control.